Volatilidade da taxa de câmbio real e taxa de juros no Brasil: Evidências de um modelo VAR-GARCH-M para o período 1999-2010 - Vinícius dos Santos Cerqueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper investigates the relationship between interest rate and volatility of real effective exchange rate in Brazil. Through a simultaneous multivariate GARCH model, which allows estimating equations for the mean and variance in a single stage, it was observed that: it's not possible to say that the percentage change in real effective exchange rate, its volatility and interest rate (Selic and Selic discounted the inflation calculated by IPCA) are independent. Under the regime of inflation targeting, this account suggests that the high exchange rate volatility in Brazil may be related to the monetary policy rule adopted in the country.
Keywords: E; E49; 330; Zins; Kaufkraftparität; Volatilität; Inflationssteuerung; Geldpolitik; Regelbindung; Brasilien